Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1024/1421-0185/a000139
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Landmark Modality and Familiarity in Human Wayfinding

Abstract: What characteristics constitute a “helpful” landmark for wayfinding and how are they represented in the human brain? Experiment 1 compared recognition and wayfinding performance for visual, verbal, and acoustic landmarks (animals) learned in our virtual environment SQUARELAND. Experiment 2 investigated landmark semantics, namely, famous versus unfamiliar buildings. The results showed that, first, the best recognition performance was observed for words (verbal condition) followed by sounds. Performance was wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…To systematically investigate this question, we used our virtual environment S quareland (Hamburger & Knauff, ; Fig. left), which has successfully been employed in many previous experiments of our research group (Hamburger & Röser, ; Karimpur & Hamburger, ; Röser, ; Röser et al, ). S quareland basically consists of a 10 × 10 block raster with orthogonal intersections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To systematically investigate this question, we used our virtual environment S quareland (Hamburger & Knauff, ; Fig. left), which has successfully been employed in many previous experiments of our research group (Hamburger & Röser, ; Karimpur & Hamburger, ; Röser, ; Röser et al, ). S quareland basically consists of a 10 × 10 block raster with orthogonal intersections.…”
Section: Methodsmentioning
confidence: 99%
“…In several experiments, we demonstrated that wayfinding performances based on visual, auditory, and semantic cues are comparable and that such cues are almost equally suitable for spatial orientation. Overall, spatial cognition researchers seem to have a strong bias towards vision, which we have criticized several times (Hamburger & R€ oser, 2014;Knauff, 2013;R€ oser et al, 2011). So, can odors also serve as landmarks in human wayfinding?…”
Section: Olfactory Cues In Landmark-based Wayfindingmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume visual salience – that is how much an object stands out from its immediate surrounding (e.g., Caduff and Timpf, 2008) – and semantic salience of landmarks – that is for example its name, meaning, or function (Raubal and Winter, 2002; Nothegger et al, 2004; Hamburger and Knauff, 2011) – to be less important than the structural salience (Hamburger and Röser, 2011, 2014; Röser et al, 2012a). Therefore, we here try to control for these aspects and rather focus on the structural aspects as we have done in previous experiments on structural salience in which we used a route-continuation paradigm (Röser et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is research in the broader field of psychology which challenges the idea of visual cues to be most important in all cases. Hamburger and Röser (2014) analyze the influence of landmark modality (visual, acoustic, etc. ), familiarity and famousness of buildings on recognition time and wayfinding performance.…”
Section: Discussing the Resultsmentioning
confidence: 99%